Genitourinary Tuberculosis: A Rare Cause of Obstructive Uropathy in Pregnancy - Emily H. Adhikari; Elaine L. Duryea; Martha W.F. Rac; Jeanne S. Sheffield (Hindawi Limited, 2014)
Background. A rare but morbid form of extrapulmonary tuberculosis (TB), genitourinary TB is an important cause of obstructive uropathy and is likely underdiagnosed in pregnancy. Case. A 30-year-old primigravida undergoing treatment for active pulmonary TB presented with anuria at 13-14-weeks gestation. Bilateral ureteral strictures above the level of the ureterovesicular junctions were seen on imaging studies. Given her pulmonary disease, her obstructive uropathy was attributed to genitourinary TB. Bilateral percutaneous nephrostomy tubes were placed during pregnancy with successful ureteral reimplantation postpartum. Conclusion. Genitourinary TB should be considered as an etiology of urinary tract pathology during pregnancy, especially in foreign-born and immunocompromised persons. Early recognition resulting in prompt treatment can prevent further deterioration of maternal renal function and optimize pregnancy outcomes.